2014
DOI: 10.1051/0004-6361/201322994
|View full text |Cite
|
Sign up to set email alerts
|

Planet-induced disk structures: A comparison between (sub)mm and infrared radiation

Abstract: Context. Young giant planets, which are embedded in a circumstellar disk, will significantly perturb the disk density distribution. This effect can potentially be used as an indirect tracer for planets. Aims. We investigate the feasibility of observing planet-induced gaps in circumstellar disks in scattered light. Methods. We perform 3D hydrodynamical disk simulations combined with subsequent radiative transfer calculations in scattered light for different star, disk, and planet configurations. The results are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, such observations enable us to study another intriguing type of temporal variability: variations in the brightness distribution due to the orbital motion of asymmetric features in the disk. These asymmetries, such as spiral density arms and local hot spots, may result from planet-disk interactions, allowing us to derive planetary and disk parameters (Brunngräber & Wolf 2018;Ruge et al 2014Ruge et al , 2013Wolf & D'Angelo 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such observations enable us to study another intriguing type of temporal variability: variations in the brightness distribution due to the orbital motion of asymmetric features in the disk. These asymmetries, such as spiral density arms and local hot spots, may result from planet-disk interactions, allowing us to derive planetary and disk parameters (Brunngräber & Wolf 2018;Ruge et al 2014Ruge et al , 2013Wolf & D'Angelo 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of a gap can be used to infer properties of the disk (Paardekooper & Mellema 2004;Fouchet et al 2007;Crida et al 2006), with large gaps being indicative of either massive companions or multiple companions (Espaillat et al 2014;Dodson-Robinson & Salyk 2011;Dong et al 2015). In early studies, due to numerical constraints, it was assumed that the dust and gas in a disk were well mixed, and models of observations still use this method (D'Alessio et al 1998;Ruge et al 2014). However, due to the imperfect coupling of larger dust grains to the gas, it is argued that the observed structures vary with wavelength (Rice et al 2006;Pinilla et al 2012;Zhu et al 2012;Gonzalez et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Wolf & D'Angelo (2005) and Ruge et al (2013) showed the possibility of tracing gaps in continuum re-emission light for various disk configurations and ALMA configurations. In addition, Ruge et al (2014) investigated the feasibility of tracing gaps in continuum re-emission maps and scattered light images simultaneously. In contrast to this, only a few studies exist investigating the feasibility of tracing planet-induced structures through molecular line observations.…”
Section: Introductionmentioning
confidence: 99%